Making of Body Lotion from Ziziphus Mauritiana Extract - Mentari, Rezky Ayu; Qalby, Besse Nurul; Maulidia, Aprindah Nur; Fachnesya, Nindy; Nurhajawarsi, Nurhajawarsi; Sitanggang, Boy Chandra (Jurnal Sains dan Teknik Terapan, 2025)
Bidara leaves (Ziziphus mauritiana) contain active compounds such as flavonoids, tannins and saponins which function as antioxidants and antibacterials for healthy skin. This research aims to develop a body lotion formulation made from bidara leaf extract with tests including phytochemical, pH, spreadability, homogeneity, water content and organoleptic tests. Phytochemical results showed the presence of flavonoids, alkaloids, terpenoids, saponins and tannins. Three formulations were tested with different concentrations of bidara leaf extract, namely F1 (1%), F2 (3%), and F3 (5%). Test results show that the pH of all formulas (F1: 5.7; F2: 5.5; F3: 5.4) is within the SNI standard range (3.5–8.0). Spreadability decreases as concentration increases, namely F1 (7 cm), F2 (6.4 cm), and F3 (5.7 cm). All formulas met the homogeneity criteria, while the highest water content was found in F1 (49.05%) compared to F2 (26.3%) and F3 (25.6%). Organoleptic tests show that aroma resistance reaches 100% and there is no irritation in all formulas. The preferred aroma was higher in F3 (63.3%) compared to F2 (46.7%) and F1 (43.3%). Fragrance levels were similar for F1 and F3 (53.3%) as well as F2 (50%). The preferred humidity was highest in F2 (53.3%) followed by F3 (50%) and F1 (33.3%), while the permeability was highest in F3 (50%) compared to F1 (43.3%) and F2 (40%).